Daniel Tiger's Neighborhood : Daniel Chooses to be Kind - Kalban, Rachel (New York : Simon Spotlight, 2017)
Daniel is king for the day and he spends that day being kind.
Keywords: Animals; Friendships; Kindness; Children's book